2021
DOI: 10.1021/acs.jmedchem.1c01264
|View full text |Cite
|
Sign up to set email alerts
|

Development of a 1,2,4-Triazole-Based Lead Tankyrase Inhibitor: Part II

Abstract: Tankyrase 1 and 2 (TNKS1/2) catalyze post-translational modification by poly-ADP-ribosylation of a plethora of target proteins. In this function, TNKS1/2 also impact the WNT/β-catenin and Hippo signaling pathways that are involved in numerous human disease conditions including cancer. Targeting TNKS1/2 with small-molecule inhibitors shows promising potential to modulate the involved pathways, thereby potentiating disease intervention. Based on our 1,2,4-triazole-based lead compound 1 (OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“… 66 Several TNKS inhibitors have been developed 67 , 68 such as compounds E7449 69 and STP1002 70 (structure undisclosed), which have progressed in clinical studies, even if compound E7449 behaves as a dual TNKS1–2 and PARP1–2 inhibitor. Other TNKS inhibitors such as RK287107 ( 1 ) 71 and OM-153 ( 2 ) 72 are being evaluated in preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“… 66 Several TNKS inhibitors have been developed 67 , 68 such as compounds E7449 69 and STP1002 70 (structure undisclosed), which have progressed in clinical studies, even if compound E7449 behaves as a dual TNKS1–2 and PARP1–2 inhibitor. Other TNKS inhibitors such as RK287107 ( 1 ) 71 and OM-153 ( 2 ) 72 are being evaluated in preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…To further demonstrate the high similarity between the ART domains of Aq TNKS and TNKS1, we tested the thermal stabilization with established potent and selective TNKS inhibitors that were recently benchmarked (Brinch et al, 2022). This included adenosine site binders IWR-1, G007-LK, OM-153 and compound 40 (Bregman et al, 2013; Chen et al, 2009; Leenders et al, 2021; Voronkov et al, 2013), nicotinamide-site binders XAV939, E7449, AZ6102 (Huang et al, 2009; Johannes et al, 2015; McGonigle et al, 2015) and the dual-site binder NVP-TNKS656 (Shultz et al, 2013). For all inhibitors, an increased melting temperature for both TNKS1 and Aq TNKS was observed ( Figure 5b ), underlining the structural similarity between both ART domains.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent biochemical and structural analyses described later suggested that the C-3 functionalization of the triazole ring could improve selectivity. Indeed, additional compounds were prepared by placing a heteroatom, oxygen, sulfur or nitrogen in this position, which was also derivatized while maintaining a 7-methyl (19)(20)(21)(22)(23)(24)(25) or a 5,8-dimethoxy (26)(27)(28)(29)(30)(31) substitution pattern in the benzene ring (Table 3).…”
Section: Biochemical Analysis and Structural Studies Of Oul40 (1) And...mentioning
confidence: 99%
“…45 We tested multiple substituents at the C-3 position while preserving the C-7 methyl of compound 1 or the 5,8-dimethoxy of compound 14. Compounds having an oxygen (19) or small sulfur groups (20 and 22) integrated to the scaffold 1 emerged as selective against PARP10 with micromolar activities. A more interesting compound was achieved when using an amino group as C-3 substituent that resulted in 21 showing nanomolar activity against PARP10 (IC50 = 180 nM) and PARP15 (IC50 = 300 nM) with a clear selectivity towards the mono-ARTs over the poly-ARTs PARP2 and TNKS2, which were inhibited only with micromolar potencies (IC50 = 1.6 µM and 5.7 µM, respectively).…”
Section: Oul40 (1) Analogs: Biochemical Analysis and Structural Studiesmentioning
confidence: 99%
See 1 more Smart Citation